Physiological quality and dormancy of rice seeds during storage - Garcia, Jaquelini (Revista Ciência Agronômica, 2021)
Storage is a set of techniques adopted during the off-season, aiming at conditioning the seeds to maintain their quality for the next harvest. The study of effect by storage is important to know the performance of dormancy under different environments and the infl uence of temperature and relative humidity in the storage on rice seeds. Therefore, the objective was to evaluate the physiological quality of seeds in storage, to understand whether environmental conditions infl uence in overcoming dormancy and the physiological quality of rice seeds. The experiment was conducted in a completely randomized design in a factorial scheme: storage x evaluation times x cultivar. Seeds of rice cultivars from the Alto Vale do Itajaí, SC, from the 2016/17 and 2017/18 seasons were submitted to storage in a dry chamber (10 ºC and 50% RH) and conventional (without temperature and relative humidity control). Germination, vigor by accelerated aging and tetrazolium tests during storage were performed. Dormancy was affected by storage conditions. And it affected the germination and vigor of the seeds. It is concluded that the temperature and humidity conditions in the storage affect the overcoming of the dormancy of rice seeds. The dry chamber (10 ºC and 50% RH) favors the overcoming of dormancy and the maintenance of the physiological quality of the seeds of the rice cultivars Epagri 109, SCS121 CL, SCS122 Miura and Primoriso CL.